2017
DOI: 10.1103/physrevaccelbeams.20.042001
|View full text |Cite
|
Sign up to set email alerts
|

Design of the Compact Linear Collider main linac accelerating structure made from two halves

Abstract: Milling on two longitudinally split halves is one method to manufacture accelerating structures. This method is simple and allows one to avoid electromagnetic fields at bonding joints, making it attractive in manufacturing high-gradient accelerating structures. An X-band structure design with strong wakefield damping based on this manufacturing approach is studied in this work as an alternative design for the Compact Linear Collider (CLIC) main linac accelerating structures. The geometry of the structure is op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…This slight difference along the y axis allows the accelerating fields in the vacuum region to be almost identical and uniform. Figure 4 (b) shows that for the same DLA structure, the ratio of the peak magnetic field to the average accelerating field is 9.32 mA/V, which is much larger than that of existing metallic CLIC-G [36][37][38] structures. It is also found that strong magnetic fields are located on the metallic surface, resulting in large surface currents and hence high power loss and high pulsed surface heating temperature rise [30][31][32][33].…”
Section: Design Of a Dla Structurementioning
confidence: 90%
“…This slight difference along the y axis allows the accelerating fields in the vacuum region to be almost identical and uniform. Figure 4 (b) shows that for the same DLA structure, the ratio of the peak magnetic field to the average accelerating field is 9.32 mA/V, which is much larger than that of existing metallic CLIC-G [36][37][38] structures. It is also found that strong magnetic fields are located on the metallic surface, resulting in large surface currents and hence high power loss and high pulsed surface heating temperature rise [30][31][32][33].…”
Section: Design Of a Dla Structurementioning
confidence: 90%
“…By substituting these numbers into Eq. (2), a RF-tobeam power efficiency for a DAA structure as high as rfβˆ’toβˆ’beam = 51% is reached, which is 52% higher than previously reported CLIC-G structures with an efficiency of 33.5% [7][8][9][10][11][12][13][14]. It should be pointed out that this efficiency is based on a DAA structure with an ultralow-loss tangent of 6 Γ— 10 βˆ’6 .…”
Section: Rf-to-beam Power Efficiencymentioning
confidence: 96%
“…Consideration of such a regular cell is used to generate a TM02-Ο€ mode, in which the periodic length 1 is equal to 1 = 0 /2, where 0 = 25 mm is the free-space wavelength for 0 . The iris aperture radius 0 is chosen as 0 = 3.15 mm which is comparable with that of CLIC-G structure [7][8][9][10][11][12][13][14] considering the DAA structure can be potentially used for CLIC main linac in the future. According to the optimization processing in Ref [48], the disk thickness 1 is chosen to be a quarter of the resonant wavelength in such a dielectric material.…”
Section: A Regular Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the gradient, efficiency, and cost of a TBA collider, various novel accelerating/decelerating structures have been studied: metallic two-halves structure [20,29,30], dielectric-loaded structure (DLS) [12][13][14][15]19], metameterial structure [26,31,32], photonic band gap structure [33][34][35], and many others [16,23,25,[36][37][38][39][40][41]. Among them, the DLS is a very attractive candidate for a TBA collider due of its simple geometry, low fabrication cost, high group velocity with reasonable shunt impedance, and potential to withstand GV/m gradient.…”
Section: Introductionmentioning
confidence: 99%